2019
DOI: 10.3390/bs9030031
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Orientations and Organizational Citizenship Behaviors: The Moderator Role of Perceived Discrimination in the Brexit Context

Abstract: The current study aims to explain how motivational orientations influence organizational citizenship behavior (OCB) through organizational identification considering the moderator effect of perceived discrimination. A sample of 286 Spanish immigrants in the United Kingdom was included. Main conclusions support that learning orientation shows a significant direct relation with OCB. Both performance and performance-avoid goal orientation have a statistically significant impact on OCB, and this impact is mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…With this in mind, we will explore the interaction between job involvement and social identity, as well as its effects on job satisfaction. As will be noted below, social identity refers to the part of an identity that derives from membership of certain groups, demonstrating its importance on organizational outcomes [32].…”
Section: Job Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, we will explore the interaction between job involvement and social identity, as well as its effects on job satisfaction. As will be noted below, social identity refers to the part of an identity that derives from membership of certain groups, demonstrating its importance on organizational outcomes [32].…”
Section: Job Involvementmentioning
confidence: 99%
“…Social identification is linked to positive social identity through motivational and behavioral processes. Subjects did not act according to their personal identity and instead perceived their actions based on their social identity [32].…”
Section: Group Identificationmentioning
confidence: 99%
“…fIndIngs Key oCB theories Eastman (1994) suggested that OCBs can be motivated by a variety of factors, and previous researchers (e.g., Ma et al, 2018;Martin & Topa, 2019;Yuan, 2006) have attempted to uncover relevant motivational mechanisms from multiple theoretical perspectives. One purpose of the present study is to identify fundamental theories that have been used to study OCBs in hospitality settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we anticipate that participants will link applicants' performance-approach goals to perceptions of high competence, but low warmth. Performance-avoidance goals have been linked to negative performance outcomes (Kanfer et al, 2017) and negative interpersonal outcomes (e.g., less help-giving, less organizational commitment, and citizenship behavior; Chiaburu et al, 2007;Kraemer et al, 2021;Martin & Topa, 2019). However, an applicant self-reporting a performance-avoidance goal may be perceived as modest or self-deprecating (Diekmann et al, 2015;Gerhart & Lee, 2013) and, accordingly, kind and likable (characteristics associated with warmth; Budworth, 2020;Darnon et al, 2009).…”
Section: Achievement Goals To Basic Social Impressionsmentioning
confidence: 99%